Companion Publication of the 2019 Conference on Computer Supported Cooperative Work and Social Computing 2019
DOI: 10.1145/3311957.3359439
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Accessibility of Social Media

Abstract: Social media platforms are deeply ingrained in society, and they offer many different spaces for people to engage with others. Unfortunately, accessibility barriers prevent people with disabilities from fully participating in these spaces. Social media users commonly post inaccessible media, including videos without captions (which are important for people who are deaf or hard of hearing) and images without alternative text (descriptions read aloud by screen readers for people who are blind). Users with motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Overall, these results point to the important design direction for future social media accessibility and assistive tools for individuals with TBI. Currently, social media accessibility tools primarily focus on sensory level support (primarily vision) [45,110]. However, we found that cognitive, emotional, communication impairments and altered sense of identity also posed great barriers, which need to be addressed to allow individuals with TBI to fully take advantage of potential benefits of social media.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, these results point to the important design direction for future social media accessibility and assistive tools for individuals with TBI. Currently, social media accessibility tools primarily focus on sensory level support (primarily vision) [45,110]. However, we found that cognitive, emotional, communication impairments and altered sense of identity also posed great barriers, which need to be addressed to allow individuals with TBI to fully take advantage of potential benefits of social media.…”
Section: Discussionmentioning
confidence: 98%
“…A gap also exists in the accessibility options for supporting the social and communication needs of individuals with TBI [19,53]. For example, although social media sites have been striving to include more accessibility features in their platforms, those have mostly been geared towards people with hearing and vision impairments [45,110]. In contrast, there has been relatively little attention paid to improving accessibility for individuals with cognitive disabilities, including those with TBI [14,72].…”
Section: Assistive Technology and Accessibility Options For Individua...mentioning
confidence: 99%
“…Our dataset includes privacy policies from 13 companies as listed in Table 6. This set of companies covers popular camera-based applications used by blind people, as represented in the academic literature on visual assistance (e.g., [40,64,95]) and based on our experience conducting research with blind people: Aira, Be My Eyes, BeSpecular, KNFB Reader, Lookout, LookTel MoneyReader/Recognizer, OrCam MyEye, Seeing AI, and TapTapSee. These applications support a variety of use cases, types of camera-based devices, and visual data input types (images and videos) as shown in Table 6.…”
Section: Data Collectionmentioning
confidence: 99%